Evaluation of clinical pharmacist recommendations in the geriatric ward of a Belgian university hospital - Somers A (Dove Medical Press, 2013)
Annemie Somers,1 Hugo Robays,1 Peter De Paepe,2 Georges Van Maele,3 Katrina Perehudoff,4 Mirko Petrovic41Department of Pharmacy, Ghent University Hospital, Ghent, Belgium; 2Department of Emergency Medicine, Ghent University Hospital, Ghent, Belgium; 3Department of Medical Statistics, Ghent University Hospital, Ghent, Belgium; 4Department of Geriatrics, Ghent University Hospital, Ghent, BelgiumObjective: To evaluate the type, acceptance rate, and clinical relevance of clinical pharmacist recommendations at the geriatric ward of the Ghent university hospital.Methods: The clinical pharmacist evaluated drug use during a weekly 2-hour visit for a period of 4 months and, if needed, made recommendations to the prescribing physician. The recommendations were classified according to type, acceptance by the physician, prescribed medication, and underlying drug-related problem. Appropriateness of prescribing was assessed using the Medication Appropriateness Index (MAI) before and after the recommendations were made. Two clinical pharmacologists and two clinical pharmacists independently and retrospectively evaluated the clinical relevance of the recommendations and rated their own acceptance of them.Results: The clinical pharmacist recommended 304 drug therapy changes for 100 patients taking a total of 1137 drugs. The most common underlying drug-related problems concerned incorrect dose, drug–drug interaction, and adverse drug reaction, which appeared most frequently for cardiovascular drugs, drugs for the central nervous system, and drugs for the gastrointestinal tract. The most common type of recommendation concerned adapting the dose, and stopping or changing a drug. In total, 59.7% of the recommendations were accepted by the treating physician. The acceptance rate by the evaluators ranged between 92.4% and 97.0%. The mean clinical relevance of the recommendations was assessed as possibly important (53.4%), possibly low relevance (38.1%), and possibly very important (4.2%). A low interrater agreement concerning clinical relevance between the evaluators was found: kappa values ranged between 0.15 and 0.25. Summated MAI scores significantly improved after the pharmacist recommendations, with mean values decreasing from 9.3 to 6.2 (P < 0.001).Conclusion: In this study, the clinical pharmacist identified a high number of potential drug-related problems in older patients; however, the acceptance of the pharmacotherapy recommendations by the treating physician was lower than by a panel of evaluators. This panel, however, rated most recommendations as possibly important and as possibly having low relevance, with low interrater reliability. As the appropriateness of prescribing seemed to improve with decreased MAI scores, clinical pharmacy services may contribute to the optimization of drug therapy in older inpatients.Keywords: clinical pharmacist, drug-related problems, geriatric inpatients